Analysis of genetic diversity of Zymoseptoria tritici populations in central and south-eastern Ethiopia - Tucho, Ayantu; Mekonnen, Tilahun; Ghadamgahi, Farideh; Ghosh, Samrat; Muleta, Diriba; Tesfaye, Kassahun; Wang, Eu Shang; Alemu, Tesfaye; Vetukuri, Ramesh Raju (Frontiers in Plant Science, 2025)
Septoria tritici blotch (STB), caused by the hemibiotrophic fungus Zymoseptoria tritici, is a serious threat to global wheat production, and a major bottleneck to wheat production in Ethiopia. Accurate identification and analysis of the pathogen’s genetic structure helps to develop robust STB management strategies. This study aimed at molecular identification and genetic structure analysis of 200 isolates of Z. tritici representing six populations in central and south-eastern regions of Ethiopia. A total of 165 isolates were confirmed by Sanger sequencing of the internal transcribed spacer (ITS) region of nuclear DNA (rDNA) region. The pathogen’s genetic structure was further examined using 12 simple sequence repeat (SSR) markers. The microsatellite markers were highly polymorphic and informative, with mean number of alleles (Na), effective alleles (Ne), Nei’s gene diversity of 6.23, 2.90, and 0.59, respectively. Analysis of molecular variance (AMOVA) confirmed the presence of low population differentiation (FST = 0.02), high gene flow (Nm = 14.7), with 95% of the total genetic variation residing within populations, and leaving only 5% for the among populations. The highest genetic diversity (Number of allele = 9.33, Effective number of allele = 3.4 and Nei’s gene diversity = 0.68) was observed in the Oromia special zone surrounding Finfinnee (OSZ) Z. tritici populations, followed by Arsi and North Shewa populations, indicating that these areas are ideal for multi-location wheat germplasm resistance screening, and also the pathogen genetic and genomic analyses. Cluster analyses did not clearly divide the populations into genetically separate clusters according to their geographic areas of sampling, probably due to high gene flow. The analysis revealed existence of high genetic admixture, and all the individuals shared genomic backgrounds from two subgroups (K=2). Overall, the SSR markers are highly informative and effective genetic tools for unlocking the pathogen’s genetic structure. The Z. tritici populations of central and southeast Ethiopia exhibit high genetic diversity, indicating the need to deploy durable and diverse disease management strategies. North Shewa, OSZ, Arsi and West Arsi administrative zones represent hotspots for genetic and genomic analyses of Z. tritici and excellent locations for host–pathogen interaction studies, and wheat germplasm screening for STB resistance.